Strategic alignment process and decision support systems : theory and case studies - Shimizu, Tamio, 1938- (IRM Press, 2006)
"This book deals with strategic organizational decision-making providing techniques for improving the intelligence of actions by organizational decision-makers"--Provided by publisher.